Caroli Disease (Clinical Observation) - I. G. Nikitin; A. A. Karabinenko; A. E. Nikitin; E. I. Dedov; D. G. Zhukova; E. D. Presnova; S. A. Korvyakov; R. H. Azimov; E. V. Reznik (Российский журнал гастроэнтерологии, гепатологии, колопроктологии)
The incidence of Caroli disease is estimated to be 1 case per 1 million people; as a result, there are very few available clinical observations. At the moment, the treatment of Caroli disease is limited to symptomatic therapy and the prevention of complications, as well as to corrective surgery and liver transplantation.Aim. The aim of this observation is to describe one case of a rare congenital liver disease – Caroli disease – characterised by a segmented non-obstructive fibrocystic dilation of the intrahepatic bile ducts.Key findings. A 21-year-old woman was hospitalised with the signs of a systemic inflammatory reaction, hepatosplenomegaly, jaundice, portal hypertension, hepatocellular insufficiency, as well as with the manifestations of cytolytic and cholestatic syndromes. At the age of 8, she was diagnosed with a cyst of the bile ducts, which was treated with cystoenteroanastomosis. At the age of 20, in connection with high portal hypertension, portocaval shunting was performed and a mesenteric-caval anastomosis was applied. During the present hospitalisation, an expansion of the intrahepatic bile ducts was revealed by ultrasound and MSCT of the abdominal cavity with contrast, which made it possible to diagnose Caroli disease.Conclusion. A case of Caroli disease is described, which resulted in continuously recurrent cholangitis and biliary cirrhosis. This state required liver transplantation. Caroli disease should be included in differential diagnosis in patients suffering from the fever of unknown origin and cholestasis syndrome. An early diagnosis of Caroli disease is important for preventing complications, improving the quality of life and increasing the life expectancy of patients suffering from this rare disease.